Pelatihan Cognitive Behavioral Coping Skill Pada Penerima Manfaat Panti Pelayanan Sosial Wanita Wanodyatama Surakarta - Pradina, Berlianti Husna; Hamidah, Hylda Hasymi Zahrotul; Puri, Rischa Wardiana Sekar; Hertinjung, Wisnu Sri (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The service activity aims to determine the effect of cognitive behavioral coping skills on improving coping strategy skills in beneficiaries at the "Wanodyatama" Women's Social Service Center Surakarta. Subjects are 22 beneficiaries from representatives of each room. The intervention is cognitive behavioral coping skills with material on skills for stress and how to deal with it adaptively. The activities are carried out offline through assignments, group posters, and poster presentations by group representatives. Coping strategies were measured using the strategic coping scale and the data analysis used Wilcoxon signed-rank paired sample t-test. The results showed a significant increase in the understanding of coping strategies in beneficiaries after the intervention, with the results in the pre-test and post-test of W=21,000, sig=0.008 (p<.001). Therefore, cognitive behavioral coping skills can improve the understanding of coping strategies in beneficiaries.